Design of a Web-Based Project Management Information System to Address Document Management and Meeting Scheduling Issues Using the Steepest Ascent Hill Climbing Algorithm - Muhamad Rizqo Adinugroho; Bambang Wisnu Widagdo (CV. AFDIFAL MAJU BERKAH, 2026)
This study aimed to design, implement, and evaluate a web-based Project Management Information System for CV. Surya Sejahtera to improve document management and meeting scheduling processes. The system was developed to address inefficiencies in the existing manual procedures, particularly in document storage and retrieval, meeting scheduling, and communication among administrators, employees, and clients. The system provides several key features, including user login, client registration, document management, document search and download, download logs, meeting scheduling requests, schedule validation, communication, logout, and the implementation of the Steepest Ascent Hill Climbing algorithm for scheduling optimization. The scheduling algorithm evaluates alternative meeting schedules based on heuristic values derived from several criteria, including conflict-free schedules, compliance with working hours, and proximity to the client's preferred schedule, thereby recommending the optimal meeting time. Functional testing using the Black Box method demonstrated that all 32 testing scenarios were successfully completed, indicating that all system features performed as expected. Furthermore, the User Acceptance Test (UAT) achieved a score of 92%, classifying the system as highly feasible for implementation. The findings indicate that the developed system effectively enhances work efficiency, accelerates document retrieval, reduces the risk of document loss, facilitates meeting scheduling, minimizes scheduling conflicts, and supports more structured, organized, and well-documented project management activities at CV. Surya Sejahtera.